2020
DOI: 10.3389/fmicb.2020.01201
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress, Programmed Cell Death and Microcystin Release in Microcystis aeruginosa in Response to Daphnia Grazers

Abstract: There is increasing evidence that programmed cell death (PCD) in cyanobacteria is triggered by oxidative stress and that it contributes to the survival of the cyanobacterial population such as Microcystis aeruginosa. At the same time, microcystins (MCs) released during cell lysis have been implicated in colony formation (enabled by the release of polysaccharides) in M. aeruginosa-a strategy that allows the effect of a stressor, including grazing to be avoided or decreased. This experimental research has explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 83 publications
0
14
0
Order By: Relevance
“…This is exemplified by the predator-mediated induction of STX production coupled to the increased resistance to grazers in A. minutum [7]. Thus, it is likely that the potential adverse effects of STXs on zooplankton have undergone positive selection more recently, as has been suggested for MCs by Rzymski et al [69].…”
Section: Discussionmentioning
confidence: 89%
“…This is exemplified by the predator-mediated induction of STX production coupled to the increased resistance to grazers in A. minutum [7]. Thus, it is likely that the potential adverse effects of STXs on zooplankton have undergone positive selection more recently, as has been suggested for MCs by Rzymski et al [69].…”
Section: Discussionmentioning
confidence: 89%
“…Other defense mechanisms against cyanophages include physical barriers such as natural competence and the exopolysaccharide layer ( Stucken et al, 2013 ). Interestingly, recent observations indicate the correlation between RCD and bound exopolysaccharide levels in M. aeruginosa cultures exposed to unfavorable conditions inducing oxidative stress ( Rzymski et al, 2020 ). Although in this species exopolysaccharides are known to play a role in colony formation ( Gan et al, 2012 ), they may also provide additional advantages such as protection from viral infection.…”
Section: Types and Subroutines Of Regulated Cell Death In Cyanobactermentioning
confidence: 99%
“…The kin selection scenario in this regard implies the quorum sensing in which the cells undergoing RCD are releasing signaling molecules to non-infected cells – whether such molecules exist is unknown. It has been however shown that extracellular microcystin promotes the expression of genes involved in exopolysaccharide synthesis in M. aeruginosa and that RCD in this cyanobacterium correlates with microcystin release, together suggesting that this metabolite may play a signaling role ( Gan et al, 2012 ; Rzymski et al, 2020 ). All in all, it remains of particular interest to investigate whether RCD may be induced by cyanophages and if it contributes to cyanobacterial fitness.…”
Section: Types and Subroutines Of Regulated Cell Death In Cyanobactermentioning
confidence: 99%
“…However, a lot of contradictory evidence against the sole or predominant protective role of phycotoxins was accumulated. Serious doubts come from considering the fact that cyanoprokaryotes are the most ancient phototrophs, which predate the metazoan lineage [ 83 , 98 , 99 , 100 ], and therefore, it is more likely that production of phycotoxins may be a response to specific environmental abiotic stressors [ 100 , 101 ]. For example, experiments on the influence of trace metals showed that the presence of toxin appears to give an advantage to MC-producers in the early stages of exposure to severe iron stress and may protect the cell from reactive oxygen species-induced damage [ 102 ].…”
Section: Phycotoxins—origin and Possible Biological Rolementioning
confidence: 99%
“…The presence of AEG in recent cyanoprokaryotes suggests that the ability for its production is highly conserved, and it still can have some genetic functions [ 109 ]. Additionally, some ideas on possible function of phycotoxins as sexual attractants (pheromones) or role in gene regulation, chromosome organization, intraspecific regulation, cell differentiation in colony formations and in shaping the community composition through inter- and intra-species communication were suggested [ 31 , 97 , 100 , 107 , 110 , 111 , 112 , 113 , 114 ]. However, the strain-specific and diverse laboratory and field results obtained on the physiological aide have made it difficult to generalize [ 88 ].…”
Section: Phycotoxins—origin and Possible Biological Rolementioning
confidence: 99%